Grave predictions : tales of mankind's post-apocalyptic, dystopian and disastrous destiny - Ford, Drew (Andrew); Ellison, Harlan (Dover doomsday classics, 2016)
"These compelling visions of post-apocalyptic societies and dystopian worlds include short stories by some of the most acclaimed authors of all time. Among the noteworthy contributors and their works are Stephen King's "The End of the Whole Mess," "The Pedestrian" by Ray Bradbury, and Arthur C. Clarke's "No Morning After." The first-ever apocalyptic fantasy about global warming, "The End of the World," appears here, in translation from Eugene Mouton's 1872 French-language original. "The Pretence," by Ramsey Campbell, questions the nature and structure of everyday life in the aftermath of a doomsday prediction. In addition, thought-provoking stories by Philip K. Dick, Kurt Vonnegut, Jr., Greg Bear, Erike Satifka, and others offer an end-of-the-world extravaganza for fans of science fiction, horror, and fantasy"--